The effects of acute angle closure crisis on corneal endothelial cells in patients with type 2 diabetes mellitus - Cong, Lin; Pan, Xiaojing; Xia, Yiping; Zhang, Yangyang; Cheng, Jun; Dong, Yanling (Frontiers in Endocrinology, 2022)
Objective This study investigated the effects of acute angle closure crisis (AACC) on the corneal endothelial cells in patients with type 2 diabetes mellitus (DM) to identify the factors that cause corneal endothelial cell injury. Methods We examined 154 patients who visited Qingdao Eye Hospital for AACC in one eye (154 eyes; 28 men and 126 women; mean age of 68±8 years). We divided the participants into non-DM, DM well-control, and DM poor-control groups, with the unaffected eyes used as controls. Each participant was evaluated at the hospital while under AACC. We measured the relevant index and corneal parameters of the participants for statistical analysis. Results There were significant statistical differences in corneal parameters among the three groups. The decreased levels of central endothelial cell density (CD) and the percentage of hexagonal cells (6A) were statistically relevant among the groups (P<0.05). The AACC duration was correlated with CD loss rate among the groups (P<0.05). The DM duration was correlated with CD loss rate in the DM well-control group. Compared with the non-DM group, the level of 6A decreased more significantly in the DM group after AACC (P<0.05). The AACC duration in the DM well-control group was significantly shorter than in the non-DM and DM poor-control groups (P<0.001). The DM poor-control group showed significantly worse visual acuity when compared with the other groups (P<0.05). Conclusions DM may impact the functional status of corneal endothelial cells. AACC can worsen the corneal endothelium damage in patients with DM. Blood glucose levels and the duration of intraocular hypertension are closely related to the severity of corneal endothelial injury.